ANALISIS FAKTOR-FAKTOR MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Ruslan Ruslan (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2020)
This study aims to determine whether profitability, sales growth, asset structure and liquidity affect the capital structure of manufacturing companies listed on the IDX in 2018. Data collection uses secondary data obtained from financial statements using purposive sampling techniques. The population is 170 manufacturing companies registered on the IDX in 2018, while the sample taken is 113. The results of the research variable data have been tested with the classic assumption test in the form of normality and heteroscedasticity tests. The method of data analysis uses multiple linear regression techniques. The results showed simultaneously that profitability, sales growth, asset structure and liquidity had a significant effect on capital structure. The results of the research partially showed that profitability and sales growth had no effect on capital structure. While the structure of assets and liquidity has a negative and significant effect on capital structure.